Liofilisasi Hemolisat Packed Red Cell Limbah Darah Palang Merah Indonesia dengan Penambahan Lioprotektan sebagai Alternatif Standar Hemoglobin - Supriyanta, Bambang; Rahmawati, Ullya; Martsiningsih, Martha Atik; Pudyastuti, Rita Rena (Poltekkes Kemenkes Maluku, 2023)
Lyophilization of PRC waste added with 20% sucrose as lyoprotectant. This study aimed to create an alternative Hb standard, replacing the manufacturer's Hb standard. This study used an experimental with pre and posttest without control group design. PMI blood waste PRC was processed into hemolysate, added with lyoprotectant, lyophilized, checked Hb levels using the Cyanmethemoglobin method as a grouppre test, stored at 4OC for six months, checked Hb levels with the Cyanmethemoglobin method as a grouppost test. Homogeneity Test and Stability Test were carried out according to ISO 13528:2015. The average Hb level of PRC lyophilisate before storage (Xr)=15.06 g/dl, obtained Ss≤0.3σpt, so that it was declared homogeneous according to the homogeneous acceptability value according to ISO 13528: 2015. After being stored for six months at 4OC, the average level of Hb lyophilisate PRC (Yr) =14,68 g/dl, obtained |Xr-Yr| ≤ 0.3σpt so that it was declared stable according to the stable acceptability value according to ISO 13528: 2015. Hb levels of PRC lyophilisate were stated to be homogeneous and stable for six months. Hb standard from PRC lyophilisate can be used as an alternative to commercial Hb standard.